APPLYING AUTHENTIC MATERIALS IN TEACHING LEARNING ENGLISH - Merlin Helentina Napitupulu (Jurnal Mantik Penusa, 2016)
This research is action research conducted in STIE LMII Medan. The subjects of the study were 34 students of second semester in academic year 2015/2016. The data of this research were qualitative in nature and quantitative as the supporting data. The qualitative data were collected by observing the teaching and learning process during the implementation of the action, interviewing the students and the English lecturer, and taking pictures of the teaching and learning process. The instruments used in this research were interview guidelines, observation sheet and camera. The results in this research show that the applying of authentic materials is effective to improve the students’ ability in learning English especially reading comprehension. The applying of these materials is effective when they were used together with authentic tasks which provide communicative activities. After the actions were implemented, the students showed some improvements. They could focus on the lesson and actively participated in the teaching and learning process. They got familiar with some reading strategies and could apply them. They were able to scan the detail information of the texts, deduce the meaning of unfamiliar words and understand information when not explicitly stated. They had more interest and motivation in reading. All the various activities made the class atmosphere more interesting.  Key Words: Learning English, authentic material